Excepción preliminar planteada en el asunto referido a la obligación de negociar un acceso al océano Pacífico (Bolivia vs. Chile) - Abugattas, Gattas (2016)
In the handling of the contentious proceedings before the International Court of Justice (ICJ) initiated by Bolivia against Chile, regarding the obligation to negotiate access to the Pacific Ocean, the latter State lodged a preliminary objection concerning the ICJ’s jurisdiction. The paper makes a brief analysis of the preliminary objections’ regulation in the Rules of the ICJ, summarizes the Chilean arguments that supported their objection to the ICJ’s jurisdiction, shows Bolivian counterarguments and presents both the arguments and the final decision of the ICJ. The document ends with the author’s comments on the position of the parties and the judgment of the ICJ.